Toxocara vitulorum in a bison (Bison bison) herd from western Canada - Woodbury, Murray R. (Canadian Veterinary Medical Association, 2012)
The discovery of the parasite Toxocara vitulorum in bison calves in the province of Manitoba, Canada is discussed. This parasite is more commonly found in the small intestines of bovid calves living in tropical and subtropical regions of the world. This is the first time that Toxocara vitulorum has been reported from hosts in Canada.